تقييم كتاب تعليم اللغة العربية بجامعة سونان كونونج جاتي الإسلامية الحكومية باندونج إندونيسيا - Izzudin Musthafa (Jurnal Pendidikan Islam, 2015)
This study departed from the reality that until now has not found an Arabic teaching material both in Universities. The purpose of this study is 1) to determine the characteristics of teaching materials that have been used in UIN SGD Bandung; 2) to develop the Arabic language teaching materials more relevant to UIN SGD Bandung. The method used in this research is descriptive analytic method. The technique used for collecting data are observation, interview and literature study. From the results of this study concluded that the teaching materials used in UIN SGD Bandung is not relevant to the purpose of learning Arabic in UIN SGD Bandung, because Arabic teaching materials tend to be more concerned with writing skills and reading and ignoring the listening and speaking skills.